Flood Preparedness Assessment Among Flood-Prone Communities in Medan - Sembiring, Robi Arianta; Hasibuan, Gina Cynthia Raphita; Sembiring, Dicky Andrea (International Journal of Architecture and Urbanism, 2025)
The problem of flooding is one of the important tasks that must be completed in the city of Medan. Flood disasters have the potential to cause casualties, so it is important to know the level of community readiness in dealing with flood disasters. This study aims to include the involvement of the community in flood-prone areas in the city of Medan and compare the readiness of each urban districts in dealing with floods. This has a long-term goal to minimize the negative impact of flooding in the city of Medan with a bottom-up approach. The research will use a quantitative approach, namely a questionnaire to 200 respondents consisting of households that are in flood-prone locations at several points in the city of Medan. The primary data obtained from the questionnaire will be analyzed and tested for face validity. The final result of the research is expected to be able to project the level of community readiness in the city of Medan in dealing with floods and become a reference for policy makers related to flood disaster management in the city of Medan. It can be concluded from the preliminary result that Aur Urban Village has the highest value in terms of level of preparedness in comparison to the other 9 urban villages. The informality of Aur Urban Village is argued to have a significant correlation with the high level of preparedness from the residents in Aur Urban Village. keywords: Flooding, community readiness, disaster management, preparedness, buttom-up approach.